The Influence of Principal Leadership and Teacher Personality Competence on Student Learning Motivation in State Junior High Schools in Meureubo District, West Aceh Regency - Rosmaniar, Rosmaniar; Zahraini, Zahraini; Akmaluddin, Akmaluddin (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study aims to identify how influential the principal's leadership and teacher's personality competency are on the learning motivation of students at State Junior High Schools in Meureubo District, Aceh Besar Regency. This study uses a quantitative approach with a correlation research type because it wants to see the cause and effect or influence between variables, namely the influence of principal leadership, teacher's personality competency on student learning motivation. Based on the results of the analysis and identification that have been carried out, it is proven that the principal's leadership and teacher's personality competency have a significant effect on the learning motivation of students at State Junior High Schools in Meureubo District, Aceh Besar Regency, as evidenced by the R Square value of 38.8%.